Pengelolaan Program Tahfidz Al-Qur’an dalam Meningkatkan Karakter Religius Peserta Didik (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the management of the Qur’an memorization (tahfidz) program in enhancing students’ religious character. This research employed a qualitative approach using a library research method, with data collected from books, scholarly journals, and relevant previous studies. The findings indicate that the management of the tahfidz program involves interconnected stages, namely planning, implementation, evaluation, and follow-up. The planning stage has not been fully based on a comprehensive needs analysis and is not optimally integrated with religious character development. The implementation has been carried out through tahsin, tahfidz, and muroja’ah activities; however, it still faces challenges such as limited time allocation, diverse student abilities, and a lack of instructional innovation. Evaluation tends to focus primarily on memorization outcomes and has not been conducted comprehensively, resulting in suboptimal follow-up actions. The integration of the tahfidz program with religious character formation is crucial in internalizing Qur’anic values into students’ daily lives. Overall, the tahfidz program has a positive impact on improving students’ worship habits, discipline, responsibility, and moral behavior, although its effectiveness largely depends on the quality of program management and environmental support. Keywords: tahfidz program, religious character, Islamic education management, moral development, students